ADDRESSING CHALLENGES IN INTENSIVE LANGUAGE TEACHING - Abduvahobov Zokir; Safarova Dildova (Ustozlar uchun, 2025)
This article explores the key challenges faced in intensive language teaching and presents practical solutions to overcome them. It highlights the importance of balancing speed with comprehension, learner motivation, and teacher workload. The article also discusses issues related to curriculum design, assessment, and learner diversity. Recommendations are made for more effective teaching strategies, resource usage, and technological tools. The insights provided aim to support language educators in creating efficient, inclusive, and goal-oriented intensive language programs.